Menopausal hormonal therapy and ovarian cancer—an update: a literature review - Mohsen MA Abdelhafez; Karim AM Ahmed; Nashwa AM Ahmed; Mohd Hamdy Ismail; Mohd Nazri Bin Mohd Daud; Ayaa M Eldisty; Mohd Fariz Bin Amri; Mohammad Saffree Jeffree; Fairrul Kadir; Dg Marshitah Pg Baharuddin; Mohammed Firdaus Bin Bolong; Firdaus Hayati; et al. (Jaypee Brothers Medical Publishers Pvt. Ltd., 2025)
Menopausal hormone replacement therapy (MHT/HT) was the recommended course of treatment for regulating menopause before 2002 when publishing the Women’s Health Initiative (WHI). Menopausal hormone replacement therapy (MHT/HT) and the WHI were the recommended courses of treatment for regulating menopause before 2002. This study aims to evaluate previous studies looking at the connection between MHT consumption and ovarian cancer risk and subanalyze the magnitude of this risk (if any) according to the type of hormone used and other confounders. A systematic search was accomplished through medical databases such as PubMed, Medline, Google Scholar, Web of Science, and others to gather the most recent and relevant articles investigating the issue to build up a body of evidence-based recommendations and guidelines required by women’s carers to counsel and prescribe MHT for postmenopausal women who opted to use these medications. The study concluded that, following the publishing of the outcomes of WHI trials, many countries had seen a dramatic decrease in MHT prescription because of raised suspicions of increased risks of developing gynecological cancers associated with its use. The major worries were linked to breast and ovarian cancers as well as endometrial cancer for unopposed estrogen therapy users.